A new species of Astragalus section Laguropsis (Fabaceae: Galegeae) from a cross-border highland region of Altai Mountains in Russia and Mongolia - Pyak, Andrei I.; Pyak, Elizaveta A. (Phytotaxa, 2019)
Astragalus admirabilus Pyak & E.Pyak (Fabaceae: Galegeae), a new species from a cross-border highland region of Altai Mountains in Russia and Mongolia, is described and illustrated. This species belongs to section Laguropsis. Diagnostic morphological characters for discriminating this new species from closely similar A. zaissanensis and A. dilutus are tabulated. It differs from A. zaissanensis by the colour of the corolla (yellowish-white with purple keel and purple upper part of the standard vs. yellow) and its longer pods (13–14 vs. 10 mm). It differs from A. dilutus by its larger flowers (23–25 vs. 17–20 mm), its shorter peduncles (shorter than leaves vs. equal or longer than leaves) and number of flowers per inflorescence (5–8(–9) vs. 15–20). Notes are presented on the distribution, ecology and conservation status of the new taxon.